Pharmacological effect of walnuts consumption on metabolic syndrome: a current view - Ofor, Casimir C.; Ohanme, Eugene O.; Nwakelu, Benjamin N.; Ofornakara, Uzochukwu; Aja, Daniel O.; Shu, Elvis N.; Ghasi, Samuel I. (International Journal of Basic & Clinical Pharmacology, 2024)
Cardiovascular disease (CVD) is the leading cause of death worldwide (WHO, 2017). In addition to the global and national morbidity and mortality burdens of the disease, it imposes a substantial economic burden on society. The American heart association predicts that by 2035, 45% of Americans will suffer from CVD with costs expected to reach 1.1 trillion annually. Clinical trials have demonstrated that a nut-containing diet low in saturated fat and cholesterol, while high in poly and monounsaturated fatty acids has a beneficial effect on plasma lipids and lipoproteins when compared with either a low fat or average American diet. Other bioactive compounds present in walnuts, including micronutrients, fiber, and phytochemicals, may also contribute to their cardio protective effect by reducing inflammation, improving vascular reactivity, and lowering oxidative stress. It has been demonstrated that the consumption of walnuts resulted in significant reduction in body mass index (BMI), percentage of body fat, increased lean body mass and an increased amount of water in the body. A large population cohort study also demonstrated a marked reduction in body weight and other anthropometric parameters in people on regular consumption of walnuts.